Titanium hydrazinediido half-sandwich complexes: highly active catalysts for the hydrohydrazination of terminal alkynes at ambient temperature - Weitershaus, Katharina; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2009)
Reaction of [Cp*Ti(NXylN)(NtBu)(NH2tBu)] with 1 molar equiv of diphenylhydrazine yielded the hydrazinediido complex [Cp*Ti(NXylN)(NNPh2)(NH2tBu)] (1a), whereas the orange pyridine adduct [Cp*Ti(NXylN)(NNPh2)(py)] (1b) was obtained by reacting the imide [Cp*Ti(NXylN)(NtBu)(NH2tBu)] with diphenylhydrazine in the presence of pyridine. The tert-butylamine coordinated to the metal center in 1a could be removed by heating the solid at 60 °C and 10−6 mbar for 72 h, yielding [Cp*Ti(NXylN)(NNPh2)] (1c). In the presence of pyridine or 4-dimethylaminopyridine (dmap) as neutral co-ligands the hydrazinediido complexes [Cp*Ti(NXylN)(NNMePh)(py)] (2a) and [Cp*Ti(NXylN)(NNMePh)(dmap)] (2b) as well as [Cp*Ti(NXylN)(NNMe2)(dmap)] (3) were prepared. Upon replacement of dmap by the weaker donor ligand pyridine in the synthesis of the pyridine adduct analogous to 3, a mixture of [Cp*Ti(NXylN)(NNMe2)(py)] (4a) and the dinuclear complex [Cp*2Ti2(NXylN)2(μ-η1,η1-NNMe2)(μ-η1,η2-NNMe2)] (4b) was obtained. Reaction of the dimethylhydrazinediido complex 3 with phenylacetylene gave the Markovnikov cycloadduct, which had sufficient lifetime to allow its 1H, 13C, and 15N NMR spectroscopic characterization in solution. All three hydrazinediido compounds 1a, 2a, and 3 were found to display remarkable activities in catalytic hydrohydrazinations at ambient temperatures. For catalyst loadings of 5 mol % complete conversions of the terminal alkynes and diynes with Markovnikov regioselectivities of over 99% selectivity were observed within 1 h.